Adjusted and Controllability Properties of Memristor Rucklidge System - Hongyan, Zang; Lili, Huang; Shourong, Zhang; Annie, Joseph; Haiyan, Fu; Tengfei, Lei (2023)
There are many models of memristors, but there are no reports on exponential memristors. In this paper, a threedimension memristor Rucklidge system with exponential memristor is proposed by introducing exponential function and constructing exponential memristor. The dynamic behavior of the system is analyzed by means of Lyapunov exponent and bifurcation diagram. The complex attractor coexistence and amplitude modulation characteristics of the system are found. The internal variable of memristor is introduced into the second two-dimensional equation as a feedback term, and a conditional symmetric system is constructed for the three-dimensional memristor system, which can realize the polarity control of output signal. By discussing the dynamic characteristics of exponential memristor chaotic system and the control mechanism of amplitude modulation, bias and conditional symmetry, the complex dynamic characteristics of exponential function memristor are revealed, which lays a foundation for its application in the field of secure communication.